Clinical performance study of a fecal bacterial signature test for colorectal cancer screening - Malagón, Marta; Alwers, Elizabeth; Oliver, Lia; Ramió-Pujol, Sara; Sánchez-Vizcaino, Mireia; Amoedo, Joan; Cambra, Salomé de; Serra-Pagès, Mariona; Castells, Antoni; Aldeguer, Xavier; Garcia-Gil, Jesús; Brenner, Hermann (PLOS ONE, 2023)
The fecal immunochemical test (FIT) is the most widely used test for colorectal cancer (CRC) screening. RAID-CRC Screen is a new non-invasive test based on fecal bacterial markers, developed to complement FIT by increasing its specificity. The test was previously clinically evaluated in FIT-positive patients (>20 μg of hemoglobin/g of feces, “FIT20”), in which it reduced the proportion of false positive results by 16.3% while maintaining most of FIT20’s sensitivity. The aim of this study was to compare the sensitivity and specificity of a CRC screening program using RAID-CRC Screen in addition to FIT20 as a triage test in a European screening population undergoing screening colonoscopy with a CRC screening program with FIT20 alone in the same cohort. A cohort of 2481 subjects aged > 55 years from the German screening colonoscopy program was included. The colonoscopy findings were used as the gold standard in calculating the diagnostic capacity of the tests and included 15 CRC and 257 advanced neoplasia cases. RAID-CRC Screen added to FIT20 provided the same sensitivity as FIT20 alone (66.7%) in detecting CRC and a significantly higher specificity (97.0% vs. 96.1%, p<0.0001). The positive predictive value was 11.9% when using RAID-CRC Screen and 9.5% with FIT20 alone, and the negative predictive value was 99.8% in the two scenarios. For advanced neoplasia detection, the use of RAID-CRC Screen yielded significantly lower sensitivity than with FIT20 alone (17.5% vs. 21.8%, p = 0.0009), and the overall specificity was significantly higher when using RAID-CRC Screen compared with FIT20 alone (98.2% vs. 97.8%, p = 0.0039). Our findings confirm the results obtained in previous clinical studies in a CRC screening setting, showing the potential of RAID-CRC Screen to increase the overall specificity of FIT-based screening.